2012
DOI: 10.1371/journal.pone.0041582
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Corticosteroid Sensitivity by p38 Mitogen Activated Protein Kinase Inhibition in Peripheral Blood Mononuclear Cells from Severe Asthma

Abstract: BackgroundSevere asthma accounts for a small number of asthmatics but represents a disproportionate cost to health care systems. The underlying mechanism in severe asthma remains unknown but several mechanisms are likely to be involved because of a very heterogeneous profile. We investigated the effects of a p38MAPK inhibitor in corticosteroid sensitivity in peripheral blood mononuclear cells (PBMCs) from severe asthmatics and the profile of its responders.Methodology/Principal FindingsCorticosteroid sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 39 publications
(60 reference statements)
7
83
2
1
Order By: Relevance
“…Different groups have shown that GR phosphorylation at S226 is an important inhibitory mechanism of GC function, although some controversy exists regarding the nature of upstream kinases involved (6,14). For example, in some reports, c-Jun N-terminal kinase (JNK) MAPK-induced GR phosphorylation at S226 was found to inhibit GR function (6,12), whereas other studies identified p38 MAPK as another potential kinase regulating phosphorylation of GR at S226 and inhibiting its function (11,23). In contrast to these latter studies, we found that p38 MAPK negatively regulates GR phosphorylation on S211 but had no effect on S226 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different groups have shown that GR phosphorylation at S226 is an important inhibitory mechanism of GC function, although some controversy exists regarding the nature of upstream kinases involved (6,14). For example, in some reports, c-Jun N-terminal kinase (JNK) MAPK-induced GR phosphorylation at S226 was found to inhibit GR function (6,12), whereas other studies identified p38 MAPK as another potential kinase regulating phosphorylation of GR at S226 and inhibiting its function (11,23). In contrast to these latter studies, we found that p38 MAPK negatively regulates GR phosphorylation on S211 but had no effect on S226 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK is activated by upstream MAPK kinases (MKK3 or MKK6) in response to a number of inflammatory or environmental signals (17)(18)(19). Different reports have convincingly implicated p38 MAPK pathways in the pathogenesis of patients with asthma, in particular those with severe disease (20)(21)(22)(23)(24). The exact role of p38 MAPK in GR functions in human diseases has just started to emerge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several p38 mitogen-activated protein kinase (MAPK) inhibitors restore corticosteroid sensitivity in peripheral blood mononuclear cells (PBMCs) and alveolar macrophages from patients with severe asthma 63,66 . A phase II trial is registered as investigating the efficacy and safety of the inhaled p38MAPK inhibitor AZD7624 in corticosteroid resistant asthma (ClinicalTrials.gov Identifier: NCT02753764) 33 .…”
Section: Protein Kinase Inhibitorsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Protein kinase inhibitors Inhibition of protein kinase, such as p38MAPK, narrow spectrum kinase and tyrosine kinase, that are involved in cellular signaling of pro-inflammatory cytokines, may have a role in the treatment of severe asthma associated with corticosteroid insensitivity [121][122][123]. Several p38MAPK inhibitors restore corticosteroid sensitivity in PBMCs from patients with severe asthma [121,124] and COPD [125]. Clinical trials of p38MAPK inhibitors, such as oral losmapimod (GW856553) and inhaled AZD7624 are underway in COPD, although none are registered in asthma.…”
Section: Macrolidesmentioning
confidence: 99%